Visual Masking : studying perception, attention, and consciousness - Bachmann, Talis; Francis, Gregory (Burlington : Elsevier Science, 2013)
Visual masking is a technique used in cognitive research to understand pre-conscious processes (e.g., priming), consciousness, visual limits, and perception issues associated with psychopathology. This work is a short format review of research using visual masking: how it's been used, and what these experiments have discovered. It's a strategic fit to our other cognitive psychology titles. Review of research using visual masking How it's been usedWhat these experiments have discovered.
10 Uncovering the Microgenetic Mechanisms and Stages of Visual Processing by Masking11 Novel Approaches in Masking Research; 12 Masking by TMS; 13 Modeling and Theoretical Accounts of Masking; 14 Psychopharmacological and Genetic Factors in Masking; 15 Applied Aspects of Masking Research: Medicine and Technology; 15.1 Masking Methods and Psychopathology; 15.2 Studying Masking in the Context of Medicine and Technology; 16 Generalizations and Conclusions; Acknowledgments; References.
Print version record.
Keywords: Visual perception; Visual masking; PSYCHOLOGY -- Physiological Psychology; Visual masking; Visual perception; Visual Perception; Electronic books